1D reconfigurable bistable photonic device composed of phase change material for detection of reproductive female hormones. (10th December 2021) - Aly, Arafa H; Awasthi, S K; Mohamed, Asmaa M.; Al-Dossari, M.; Matar, Z. S.; Mohaseb, M. A.; El-Gawaad, N S Abd; Amin, A. F.
Abstract: In this manuscript one-dimensional (1D) photonic biosensor ( PQ ) N GDG ( PQ ) N composed of phase change material (PCM) germanium antimony telluride (GST) has been studied in visible region of electromagnetic spectrum. This design is capable of label free recognition of reproductive hormones of female which are significant during reproductive process such as menstruation and parturition. The proposed structure is composed of an air cavity separated by two buffer layers of GST material. The GST buffer layers have been used to improve the sensing performance of the structure. The modified cavity associated with buffer GST layers is sandwiched between two 1D photonic structures (PS) ( PQ ) N . Both 1D PS are consisted of alternate material layers of SiO2 and Si of period 5. The transmission spectra of proposed design have been obtained by using transfer matrix method and MATLAB software. In this work the performance of the devise has been investigated for normal and oblique incidence corresponding to TE wave only under the influence of change of phases of GST. The mainstay of this research is focused on the tunable performance of proposed bio-sensing design due to switching between amorphous phase (aGST) and crystalline phase (cGST) of GST. Moreover how the change in the thickness of cavity region as well as angle of incidence corresponding to TE wave affects the performance of the design has also been studied. The sensitivity, quality factor and figure of merit values of the design have also been studied to get deep insight about the sensing capabilities of the proposed design under the influence of crystalline and amorphous phases of GST. Thus due to simple architecture and excellent switchable and reconfigurable characteristics, our structure works efficiently in industrial and biomedical refractive index based sensing applications.